OPTIMASI PARAMETER MESIN INJECTION MOLDING TERHADAP CACAT SHORT SHOT MENGGUNAKAN RESPONSE SURFACE METHODOLOGY - Muddin, M. Hikam; Mas'ud, Mochamad (ELEMEN : JURNAL TEKNIK MESIN, 2023)
In the case study at PT XYZ Pasuruan, there is a preform production in the packaging section using an injection molding machine with the brand SIPA XFORM 500 using PET (Polyethylene Terephthalate) material. In February-April 2023, there were cases of short-shot defects in as many as 20,737 pcs of preform products. The method used in this study is RSM (Response surface methodology) by calculating using minitab21 software based on Box-Behnken experimental design. The independent variables used consisted of temperature (280 °C, 283 °C, and 285 °C), holding pressure (65 bar, 67 bar, 70 bar), and cooling time (1.8 s, 1.9 s, 2 s) so that 15 runs of experiments were obtained. From the optimization results, a temperature of 285 °C, a holding pressure of 70 bar, and a cooling time of 1.8 s. The resulting variable short-shot response of -0.0128 with a desirability value of 1.0 indicates that the program is increasingly able to produce the desired product perfectly.